The Effect of Mentoring on The Success Level of Halal Self-Declare Certification Implementation in Food Msmes in Kemang Village Bojong Picung District Cianjur Regency - Reza Fauzi Bukhori; Nisa Azzahra Nurmalika; Sabila Nur Azizah; Ramadhan Eka Putra; Addi Lukman Prabowo; Muhammad Aifa Altaman (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This article aims to analyse the effect of mentoring on the success rate of implementing self-declare halal certification in food UMKM in Kemang Village. Self-declaration of halal certification is regarded as a pragmatic solution for UMKM; however, numerous business actors continue to encounter technical impediments. The focal point of this study is the assistance provided by KKN students. The research method employed a descriptive qualitative approach, incorporating interviews and observations. The findings of the study demonstrate that the implementation of a mentorship programme is conducive to enhancing comprehension, motivation, and the thoroughness of halal certification documentation.